Select the best. Positive selection to improve farm saved seed potatoes (Georgian) - Mdivani, R.; Mosiashvili, L.; Tsiklauri, D.; Tkemaladze, L. (International Potato Center, 2018)
This training manual is designed to provide step-by step instructions to trainers in teaching potato farmers positive selection, that is, to ‘select the best’. Positive selection can be used to improve the quality of the seed potatoes saved from the farmers own crop.